Програмна система для автоматизованого контролю умов навколишнього середовища на планеті Марс - Ковальова, Н. Ю. (ХНУРЕ, 2020)
The purpose of the project is developing a software system to monitor environmental conditions on the Mars planet and to protect the colonizers from adverse living conditions. The system will control environmental parameters such as carbon dioxide in the air, humidity, temperature, atmospheric pressure and gravity in special living quarters. The system will also be able to process the received data, will report users if indicators are not standardized, and will provide pieces of advice for taking life-saving measures. The collection of statistics should assist the colonizers in analyzing of global environmental problems on the colonization planets.